(untitled) (Genta Hredaya: Media Informasi Ilmiah Filsafat Hindu, 2024)
This study aims to explore Anvīkṣikī, the classical Hindu discipline of reasoning, logic, and critical analysis as a form of epistemology that can contribute to the development of contemporary Cognitive Science. In the Indian philosophical tradition, Anvīkṣikī includes not only rational and dialectical methods, but also introspective and spiritual dimensions in understanding the process of thinking and consciousness (citta). This article presents a historical-philosophical study of the main texts containing the teachings of Anvīkṣikī, such as Kautilya’s Arthaśāstra and Nyāya-Vaiśeṣika sources, and analyzes how this epistemic framework can be compared and reconciled transdisciplinary with the main theories in Cognitive Science, such as mental representation, reflective consciousness, and embodied cognition. Using hermeneutic approaches and conceptual analysis, this study shows that Anvīkṣikī contains principles of systematic rationality that are in line with modern cognitive science approaches, but at the same time extends them with ethical and spiritual frameworks. This study offers an important contribution to the development of non-Western epistemologies in the field of mind studies and proposes a more inclusive philosophical dialogue between Eastern and Western scientific traditions.